Systematic review on the association between respiratory virus real-time PCR cycle threshold values and clinical presentation or outcomes. (23rd September 2021) - Bouzid, Donia; Vila, Jordi; Hansen, Glen; Manissero, Davide; Pareja, Josep; Rao, Sonia N; Visseaux, Benoit
Abstract: Objectives: It is unclear whether real-time (rt)-PCR cycle threshold (Ct) values can be utilized to guide clinical and infection-control decisions. This systematic review assesses the association between respiratory pathogen rt-PCR Ct values and clinical presentation or outcomes. Methods: We searched MEDLINE, EMBASE and Cochrane library databases on 14–17 January 2020 for studies reporting the presence or absence of an association between Ct values and clinical presentation or outcomes, excluding animal studies, reviews, meta-analyses, and non-English language studies. Results: Among 33 studies identified (reporting on between 9 and 4918 participants by pathogen), influenza ( n =  11 studies; 4918 participants), human rhinovirus (HRV, n =  11; 2012) and respiratory syncytial virus (RSV, n =  8; 3290) were the most-studied pathogens. Low influenza Ct values were associated with mortality in 1/3 studies, with increased disease severity/duration or ICU admission in 3/9, and with increased hospitalization or length of hospital stay (LOS) in 1/6. Low HRV Ct values were associated with increased disease severity/duration or ICU admission in 3/10 studies, and with increased hospitalization or LOS in 1/3. Low RSV Ct values were associated with increased disease severity/duration or ICU admission in 3/6 studies, and with increased hospitalization or LOS in 4/4. Contradictory associations were also identified for other respiratory pathogens. Conclusions: Respiratory infection Ct values may inform clinical and infection-control decisions. However, the study heterogeneity observed in this review highlights the need for standardized workflows to utilize Ct values as a proxy of genomic load and confirm their value for respiratory infection management.